Kinetics of Glucose Synthesis from the Peel of the King Banana (Musa textilia) by Enzymatic Hydrolysis - Muchamad Fajar Alamsyah; Sunarto, Sandy Ryan Hendrawanto; Redjeki, Sri; Erliyanti, Nove Kartika (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
Indonesia is one of the agricultural countries with an abundance of farm products, including bananas. The utilisation of banana peel waste has a very high value if used as a raw material for glucose production. One method used for glucose production is enzymatic hydrolysis. The objective of this study is to investigate the effect of liquefaction time and saccharification time on the rate of enzymatic hydrolysis reaction, as well as to determine the kinetic equation for the enzymatic hydrolysis synthesis of banana peel glucose. The stages of this study include the raw material preparation stage, the enzymatic hydrolysis stage, and the final content analysis stage. Glucose content analysis was performed using a portable refractometer. The Michaelis-Menten method was used to determine the reaction constant. This study was conducted with an initial substrate concentration of 30% (w/v) at liquefaction times of 80, 100, 120, 140, and 160 minutes. Additionally, saccharification times of 12, 16, 20, 24, and 28 hours were employed. The dextrin formed during liquefaction was 29.6%, 29.2%, 28.8%, 28.5%, and 27.8%, respectively. These dextrin levels were used as reactants in the saccharification process to produce glucose. The glucose formed from the hydrolysis of banana peel carbohydrates with a dextrin content of 29.6% and a saccharification time of 12 hours was 4.2%. The reaction rate equation formed from this process is   Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero HungerSDG 9: Industry, Innovation, and InfrastructureSDG 12: Responsible Consumption and ProductionSDG 13: Climate Action